Germination, Outgrowth, and Vegetative-Growth Kinetics of Dry-Heat-Treated Individual Spores of Bacillus Species - He, Lin (Appl Environ Microbiol, 2018)
DNA damage kills dry-heated spores of Bacillus subtilis, but dry-heat-treatment effects on spore germination and outgrowth have not been studied. This is important, since if dry-heat-killed spores germinate and undergo outgrowth, toxic proteins could be synthesized. Here, Raman spectroscopy and differential interference contrast microscopy were used to study germination and outgrowth of individual dry-heat-treated B. subtilis and Bacillus megaterium spores. The major findings in this work were as follows: (i) spores dry-heat-treated at 140°C for 20 min lost nearly all viability but retained their Ca(2+)-dipicolinic acid (CaDPA) depot; (ii) in most cases, dry-heat treatment increased the average times and variability of all major germination events in B. subtilis spore germination with nutrient germinants or CaDPA, and in one nutrient germination event with B. megaterium spores; (iii) B. subtilis spore germination with dodecylamine, which activates the spore CaDPA release channel, was unaffected by dry-heat treatment; (iv) these results indicate that dry-heat treatment likely damages spore proteins important in nutrient germinant recognition and cortex peptidoglycan hydrolysis, but not CaDPA release itself; and (v) analysis of single spores incubated on nutrient-rich agar showed that while dry-heat-treated spores that are dead can complete germination, they cannot proceed into outgrowth and thus not to vegetative growth. The results of this study provide new information on the effects of dry heat on bacterial spores and indicate that dry-heat sterilization regimens should produce spores that cannot outgrow and thus cannot synthesize potentially dangerous proteins. IMPORTANCE Much research has shown that high-temperature dry heat is a promising means for the inactivation of spores on medical devices and spacecraft decontamination. Dry heat is known to kill Bacillus subtilis spores by DNA damage. However, knowledge about the effects of dry-heat treatment on spore germination and outgrowth is limited, especially at the single spore level. In the current work, Raman spectroscopy and differential interference contrast microscopy were used to analyze CaDPA levels in and kinetics of nutrient- and non-nutrient germination of multiple individual dry-heat-treated B. subtilis and Bacillus megaterium spores that were largely dead. The outgrowth and subsequent cell division of these germinated but dead dry-heat-treated spores were also examined. The knowledge obtained in this study will help understand the effects of dry heat on spores both on Earth and in space, and indicates that dry heat can be safely used for sterilization purposes.